Answer:
x = 7
y = 3
Step-by-step explanation:
We are given two equations
2x - 7y = -7 -----------eqn 1
-5x + 6y= -17 ----------eqn 2
Let's pick eqn 1, to make y the subject of the formula
2x - 7y = -7
2x + 7 = 7y
Divide both sides by 7, to make y the subject of the formula
(2x + 7) / 7 = 7y/7
(2x + 7) / 7 = y
Substitute y into the equation 2
-5x + 6y = -17
-5x + 6(2x + 7)/7 = -17
Open the bracket
-5x + (12x + 42) / 7 = -17
LCM = 7
(-35x + 12x + 42) / 7 = -17
(-23x + 42)/7 = -17
Cross multiply
-23x + 42 = -17 * 7
-23x + 42 = -119
-23x = -119 - 42
-23x = -161
- cancels -
23x = 161
Divide both sides by 23 to get the value of x
23x / 23 = 161/23
x = 161/23
x = 7
Substitute the value of x into eqn 1
2x - 7y = -7
2(7) - 7y = -7
14 - 7y = -7
- 7y = -7 - 14
-7y = -21
Divide both sides by -7 to get the value of y
-7y/ -7 = -21/-7
Well, - cancels -
y = -21/-7
y = 3
The values are
x = 7
y = 3
We can verify our values
Let's take eqn 2 to confirm
-5x + 6y = -17
x = 7
y = 3
= -5(7) + 6(3)
= -35 + 18
= -17
Our values are correct